2012
DOI: 10.2337/dc12-0053
|View full text |Cite
|
Sign up to set email alerts
|

Skin Intrinsic Fluorescence Is Associated With Coronary Artery Disease in Individuals With Long Duration of Type 1 Diabetes

Abstract: OBJECTIVESkin intrinsic fluorescence (SIF) reflects many factors, including the presence of certain advanced glycation end products. We investigated whether SIF was associated with coronary artery disease (CAD) in type 1 diabetes and whether this relationship was independent of renal disease.RESEARCH DESIGN AND METHODSSIF was measured in 112 subjects from the Pittsburgh Epidemiology of Diabetes Complications (EDC) study and 60 from MedStar Health Research Institute when mean age and diabetes duration were 48 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 37 publications
2
32
1
Order By: Relevance
“…28,29 Previous research has shown that this SIF measure is correlated with the severity of tissuespecific diabetes related complications such as peripheral neuropathy (seen mainly in the distal lower extremities), increased arterial stiffness, and nephropathy. 25,30,31 A 2014 study by Larkin et. al reports differences in skin fluorescence, glycated hemoglobin, and functional disability between groups with and without upper extremity impairments in a sample of people with Type 1 DM.…”
mentioning
confidence: 98%
“…28,29 Previous research has shown that this SIF measure is correlated with the severity of tissuespecific diabetes related complications such as peripheral neuropathy (seen mainly in the distal lower extremities), increased arterial stiffness, and nephropathy. 25,30,31 A 2014 study by Larkin et. al reports differences in skin fluorescence, glycated hemoglobin, and functional disability between groups with and without upper extremity impairments in a sample of people with Type 1 DM.…”
mentioning
confidence: 98%
“…Comparable data collection methods were used for both cohorts for brain MRI and concurrent assessment of cognition, blood pressure, lipids, and glucose, except when noted (see reference 23 and 24 The time interval from the most recent EDC study assessments of T1DM-related complications occurred, on average, 5 years before MRI. Blood pressure, weight, height, serum glucose, and glycated hemoglobin (HbA 1C ) were obtained periodically for patients with T1DM from 1986-1988 to time of MRI, and study 20-year averages were computed.…”
Section: Measures Of Interestmentioning
confidence: 99%
“…These methods allow for a fast, reproducible, and cost-effective measurement of AGEs accumulation. 12,16,17 In this issue of Journal of Diabetes Science and Technology, Olson and coauthors 18 present data from an elegant multicenter study performed at nine U.S. centers. The main scope of the article was to evaluate the diagnostic value of SFS, FPG, and HbA1c versus a 75 g OGTT for the diagnosis of abnormal glucose tolerance (defined as a venous plasma glucose ≥140 mg/dl 2 h following an OGTT) in a population of 479 previously undiagnosed subjects at risk for developing type 2 diabetes mellitus (T2DM).…”
mentioning
confidence: 99%